Peptide based vesicles for cancer immunotherapy: design, construction and applications - Yu, Yulin; Lyu, Jiaxin; Muhadaisi, Yizimujiang; Shi, Chen; Wang, Dongyuan (Frontiers in Immunology, 2025)
Cancer immunotherapy has emerged as a powerful strategy for clinical treatment of malignant cancers. Despite the advances, cancer immunotherapy has met several challenges such as the limited efficacy to small subsets of patients, and serious autoimmune side effects. Cancer vaccines that target neoantigens to direct and amplify immune responses against tumors, have shown their efficacy and safety in preclinical and clinical researches. The developed cancer vaccines mainly contained peptide vaccines, mRNA vaccine, cell vaccine and oncolytic virus vaccine. In the last decade, both peptide based vaccines and vesicle based vaccines have attracted enormous attention for personalized vaccine development due to their potent efficacy in different tumor models. Peptide based vesicles are one kind of vesicles that are modified with functional peptides to enhance the efficiency of immune response and anti-cancer effect. In this review, we will introduce the basic characteristics, classification and biological application of vesicles or peptide based cancer vaccines respectively. Then the design and construction of peptide based vesicles will be summarized. Finally, we concluded the biological applications of peptide based vesicles in various cancer types and analyzed the key obstacles to overcome for their clinical applications. We hope this review could provide a better understanding of the construction of peptide based vesicles and their prospects for clinical applications.